Using customer-based brand equity model in the higher education context: simulating the current university’s brand - Stukalina, Yulia; Pavlyuk, Dmitry (Business, Management and Economics Engineering, 2021)
Purpose – the purpose of the article is to simulate the current version of a university’s brand using the Customer-Based Brand Equity (CBBE) model. Research methodology – the methodology of the paper includes analysis of theoretical sources and prior research on branding in higher education. For collecting primary data, a questionnaire based on the multi-dimensional CBBE model was used; a survey was conducted in Transport and Telecommunication Institute (Latvia). Structural equation modelling was then applied for confirmatory factor analysis of relationships between brand equity-related factors. Findings – Statistical analysis of the conducted survey’s data disclosed the importance of different brand dimensions within the CBBE model: Performance, Imagery, Judgments, Feelings, and Resonance. There is a notable difference between the perception of brand equity and associated factors by local and foreign students; it was discovered that local students have more concerns about the Imagery of the university brand, while foreign students are more focused on the Resonance factor. Research limitations – the research was conducted within one higher education institution. Further study with a broader research base that confirms the applicability of the Keller’s model in different settings would be beneficial. Practical implications – as brand equity affects the choice of a marketing strategy adopted by a university, the information obtained through simulation of the current version of the corresponding brand is vital for developing and updating an efficient strategy aimed at accomplishing a competitive advantage in both local and international settings. Originality/Value – the current brand’s version has been successfully stimulated in higher education settings, applying the CBBE model as a scalable framework – to demonstrate how different factors related to brand equity are perceived by the university’s students.